2018
DOI: 10.1016/s2213-2600(18)30171-1
|View full text |Cite
|
Sign up to set email alerts
|

The CF-Sputum Induction Trial (CF-SpIT) to assess lower airway bacterial sampling in young children with cystic fibrosis: a prospective internally controlled interventional trial

Abstract: SummaryBackgroundPathogen surveillance is challenging but crucial in children with cystic fibrosis—who are often non-productive of sputum even if actively coughing—because infection and lung disease begin early in life. The role of sputum induction as a diagnostic tool for infection has not previously been systematically addressed in young children with cystic fibrosis. We aimed to assess the pathogen yield from sputum induction compared with that from cough swab and single-lobe, two-lobe, and six-lobe broncho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 24 publications
3
96
0
Order By: Relevance
“…In conclusion, while nasopharyngeal swabs were superior to oropharyngeal swabs at identifying potential lower airway bacterial pathogens, neither of these swabs nor the two combined reliably “ruled in” or “ruled out” lower airway infection by any of the three main respiratory bacterial pathogens in children with PBB, CSLD, and bronchiectasis. These findings highlight the need for more reliable, noninvasive tests in young children for diagnosing lower airway infection where other methods, such as induced sputum, have not performed as well as they have in older children with CF …”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, while nasopharyngeal swabs were superior to oropharyngeal swabs at identifying potential lower airway bacterial pathogens, neither of these swabs nor the two combined reliably “ruled in” or “ruled out” lower airway infection by any of the three main respiratory bacterial pathogens in children with PBB, CSLD, and bronchiectasis. These findings highlight the need for more reliable, noninvasive tests in young children for diagnosing lower airway infection where other methods, such as induced sputum, have not performed as well as they have in older children with CF …”
Section: Discussionmentioning
confidence: 99%
“…Sputum induction using nebulized hypertonic saline is an alternative to obtain lower airway samples with minimal discomfort to the patient . Previous studies have shown that induced sputum samples correlate well with BAL samples with respect to bacterial load and pathogens isolated . In our patient cohort, four children with new NTM isolates had subsequent repeat isolation of these pathogens from BAL samples; one of them had repeat NTM isolation on sputum induction suggesting consistency of microbiological yield from sputum induction.…”
Section: Discussionmentioning
confidence: 53%
“…This is of special importance in detection of mycobacteria, which cannot be isolated from OPS. In the prospective CF‐Sputum Induction Trial (CF‐SpIT), pathogen yield from sputum induction was compared with that from OPS, single‐lobe, two‐lobe, and six‐lobe BAL . One hundred twenty‐four children with CF, aged 6 months to 18 years, had 200 sputum induction procedures, of which 84% were successful.…”
Section: Infection Detection and Epidemiologymentioning
confidence: 99%